Intracranial and extracranial multiple arterial dissecting aneurysms in rheumatoid arthritis: A case report. Issue 2 (April 2021) - Uekawa, Ken; Kaku, Yasuyuki; Amadatsu, Toshihiro; Matsuzaki, Hiroaki; Ohmori, Yuki; Kawano, Takayuki; Hirata, Shinya; Yamaguchi, Tomomi; Kosho, Tomoki; Mukasa, Akitake
Objective: We describe a case of intracranial and extracranial multiple arterial dissecting aneurysms in rheumatoid arthritis (RA). Case Presentation: A 29-year-old man with a medical history of RA since 18 years of age was admitted to our hospital for vomiting, dysarthria, and conscious disturbance. At 23, he underwent ligation of the left internal carotid artery (ICA) with superficial temporal artery to middle cerebral artery anastomosis because of acute infarct of the left hemisphere caused by arterial dissection of the left ICA. During the current admission, computed tomography (CT) revealed subarachnoid hemorrhage, and digital subtraction angiography (DSA) demonstrated dissecting aneurysms of the left intracranial vertebral artery (VA) and right extracranial VA. We diagnosed him with a ruptured dissecting aneurysm of the left intracranial VA and performed endovascular parent artery occlusion on the left VA. For the right unruptured VA aneurysm, we performed coil embolization simultaneously. At 2 weeks after the endovascular treatment, follow-up DSA revealed that multiple de novo dissecting aneurysms developed on the origin of the left VA and left and right internal thoracic arteries. Those aneurysms were treated with coil embolization. Other remaining aneurysms on the left thyrocervical trunk, right transverse cervical artery, and both common iliac arteries were treated by conservative therapy. While continuing medical treatment for RA, the patient recovered and was discharged to a rehabilitation hospital. Conclusion: Considering that RA-induced vasculitis can be a potential risk of vascular complications including multiple arterial dissections, physicians should carefully perform endovascular interventional procedures for patients with long-term RA.